2013
DOI: 10.17221/9/2013-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Development of target (crop) trees in beech (Fagus sylvatica L.) stand with delayed initial tending and managed by different thinning methods

Abstract: ABSTRACT:We evaluated the research on silviculture-production in the last 45 years in a 105-year-old beech stand, not tended up to its stand age of 60 years. Four alternatives (tending regime) were studied for development of the target (crop) trees. These were: (i) plot with heavy thinning from below (C degree according to the German Forest Research Institutes from 1902), (ii) plot with free crown thinning (thinning interval of 5 years), (iii) plot with free crown thinning (thinning interval of 10 years), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
2
9
0
3
Order By: Relevance
“…The question is whether this will be reflected on the quantity and value production of stands. Present knowledge on delayed tending in beech stands (Réh 2004;Štefančík 2013) point out that the desired dimensions (parameters) in terms of quantity of production can be more or less also achieved by delayed tending. However, it depends on the site and tending method and/or a type of thinning (Štefančík 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…The question is whether this will be reflected on the quantity and value production of stands. Present knowledge on delayed tending in beech stands (Réh 2004;Štefančík 2013) point out that the desired dimensions (parameters) in terms of quantity of production can be more or less also achieved by delayed tending. However, it depends on the site and tending method and/or a type of thinning (Štefančík 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…From the results observed in naturally regenerated beech stands (Štefančík 1984, 2013aŠtefančík & Bošela 2014;Štefančík et al 2014) it is clear that thinning based on negative selection from below resulted in better quantity of production. According to today's tending targets, early, and more or less heavy crown thinning is also recommended by Spellmann & Nagel (1996) for beech stands.…”
Section: Discussionmentioning
confidence: 99%
“…Beech stands can be influenced by thinning from the point of production parameters (e.g. Abetz & Ohnenus 1999;Tarp et al 2000;Bastien et al 2005;Boncina et al 2007;Hein et al 2007;Štefančík 2013a) but also in the frame of other forest services. Thinning in beech stands is important for the cycles of carbon (Borys et al 2013) and nitrogen (Nahm et al 2006;Dannenmann et al 2007a), and also climate (Le Goff & Ottorini 1993;Cescatti & Piutti 1998;Barna 2000Barna , 2001Lemoine et al 2002;Dannenmann et al 2007b;Štefančík 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the authors recommended to start with the tending of a stand in a very early growth phase of thicket (Réh 1968(Réh , 1969Jurča, Chroust 1973;Lüpke 1986;Korpeľ et al 1991) and/or in small pole stage stands at the very latest (Štefančík 1974). There are some experiments when tending started only in a pole stage stand (Štefančík 1974, 2013aPretzsch 2005). Results from long-term investigations showed that in the case of late, but systematic and intensive tending in beech stands it is possible to achieve satisfactory quantitative production.…”
mentioning
confidence: 99%